Abnormal lactic dehydrogenase isoenzyme patterns in ulcerative colitis with precancerous change. Issue 1 (January 1971) - Lewis, B.; Morson, B. C.; February, A. W.; Jones, J. Hywel; Misiewicz, J. J.
Abstract : The isoenzyme pattern of lactic dehydrogenase was measured in rectal biopsies from six patients with ulcerative colitis in whom precancerous histological changes had been independently recognized. There was a highly significant increase in the ratio of isoenzymes IV + V to I + II. This suggests that lactic dehydrogenase isoenzyme measurement may prove a valuable addition to histology in the recognition of precancer in ulcerative colitis.